Book review: Satija, M.P. and Kyrios, Alex. A handbook of history, theory and practice of the Dewey Decimal Classification system - Elena Maceviciute (Information Research: An International Electronic Journal)
Satija, M.P. and Kyrios, Alex. A handbook of history, theory and practice of the Dewey Decimal Classification system. London: Facet Publishing, 2023. xx, 244 p. ISBN 978-1-78330-609-1